Pengaruh Kualitas Produk, Persepsi Harga dan Brand Ambassador Terhadap Keputusan Pembelian: Studi pada Konsumen Produk Sepatu Ventela Semarang - Jessica Widyaningrum; Euis Soliha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study is used to identify components that can influence purchasing decisions through product quality, price perception and brand ambassadors. This study uses a quantitative approach with examiners sending questionnaires via Google Form to one hundred respondents. Multiple linear regression tests based on SPSS 25 statistics are used in the purposive sampling method. This study tracks consumers who have purchased Ventela products in the city of Semarang. The results show that price perception has no influence on purchasing decisions. Product quality and brand ambassadors influence purchasing decisions. Ventela shoe products in Semarang City.